Kozioł & Kozioł : katalog wystawy zorganizowanej w Muzeum w Kwidzynie - Witkowicz-Pałka, Ewa (Muzeum Zamkowe w Malborku, 2014)
Catalog of a joint exhibition of Władysław Kozioł and Wojciech Kozioł; sections printed tête-bêche. Works include paintings and designs for stained glass windows